The Court’s power to condone a document in terms of section 2(3) and section 2A of the Wills Act 7 of 1953 : a comparative analysis and recommendations - Van der Linde, Anton (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.